Variations of intracellular density during the cell cycle arise from tip-growth regulation in fission yeast - Odermatt, Pascal D.; Miettinen, Teemu P.; Lemiere, Joel; Kang, Joon Ho; Bostan, Emrah; Manalis, Scott R.; Huang, Kerwyn Casey; Chang, Fred (ELIFE SCIENCES PUBLICATIONS LTD, 2021)
Intracellular density impacts the physical nature of the cytoplasm and can globally affect cellular processes, yet density regulation remains poorly understood. Here, using a new quantitative phase imaging method, we determined that dry-mass density in fission yeast is maintained in a narrow distribution and exhibits homeostatic behavior. However, density varied during the cell cycle, decreasing during G2, increasing in mitosis and cytokinesis, and dropping rapidly at cell birth. These density variations were explained by a constant rate of biomass synthesis, coupled to slowdown of volume growth during cell division and rapid expansion post-cytokinesis. Arrest at specific cell-cycle stages exacerbated density changes. Spatially heterogeneous patterns of density suggested links between density regulation, tip growth, and intracellular osmotic pressure. Our results demonstrate that systematic density variations during the cell cycle are predominantly due to modulation of volume expansion, and reveal functional consequences of density gradients and cell-cycle arrests.